Phase 1 dose escalation multicenter trial of pracinostat alone and in combination with azacitidine in patients with advanced hematologic malignancies. Issue 24 (25th August 2017) - Abaza, Yasmin M.; Kadia, Tapan M.; Jabbour, Elias J.; Konopleva, Marina Y.; Borthakur, Gautam; Ferrajoli, Alessandra; Estrov, Zeev; Wierda, William G.; Alfonso, Ana; Chong, Toh Han; Chuah, Charles; Koh, Liang‐Piu; et al.
Abstract : BACKGROUND: Pracinostat is a potent histone deacetylase inhibitor with antitumor activity in both solid tumor and acute myeloid leukemia (AML) cell lines. Pracinostat is reported to have modest clinical activity in patients with advanced solid tumors. Given the higher preclinical sensitivity of hematologic malignancies to pracinostat, the authors conducted a phase 1 study to assess the safety, maximum tolerated dose, recommended phase 2 dose, efficacy, pharmacokinetics, and pharmacodynamics of pracinostat in patients with advanced hematological malignancies. METHODS: Pracinostat was administered orally 3 times a week for 3 weeks on a 28‐day cycle. Patients were assigned to 7 dose levels using a 3 + 3 dose escalation design. RESULTS: A total of 44 patients were enrolled, 25 of whom had AML and 14 of whom had myelodysplastic syndrome. The maximum tolerated dose was 120 mg and the recommended phase 2 dose was 60 mg. Two patients with AML achieved a response: 1 complete remission (CR) and 1 complete cytogenetic response. Despite a dose‐dependent increase in the plasma concentration of pracinostat, a similar increase in histone acetylation was not observed. As an extension, 10 additional patients with myelodysplastic syndrome were enrolled to assess the safety and efficacy of pracinostat in combination with azacitidine. Six patients achieved a CR and 3 achieved a CR without platelet recovery with no added toxicity. CONCLUSIONS: The results of the current study demonstrate that pracinostat is safe, with modest single‐agent activity in patients with hematological malignancies. Cancer 2017;123:4851‐9 . © 2017 American Cancer Society . Abstract : Pracinostat is safe, with modest single‐agent activity reported in patients with hematological malignancies. When combined with azacitidine, pracinostat has shown significant antitumor activity in patients with myelodysplastic syndrome.